2020
DOI: 10.1002/jcb.29860
|View full text |Cite
|
Sign up to set email alerts
|

SCF FBXW17 E3 ubiquitin ligase regulates FBXL19 stability and cell migration

Abstract: The Skp1‐Cul1‐F‐box protein (SCF) E3 ligase complex is one of the largest ubiquitin E3 ligase families. FBXL19, a F‐box protein in SCFFBXL19 E3 ligase complex, regulates a variety of cellular responses including cell migration. We have shown that FBXL19 is not stable and its degradation is mediated by the ubiquitin–proteasome system, while the ubiquitin E3 ligase for FBXL19 ubiquitination and degradation has not been identified. In the study, we discovered that a new ubiquitin E3 ligase, SCFFBXW17, ubiquitinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Because overexpression of FBXL19 or PDLIM2 suppresses RANKL in osteocytic cells, preventing the reduction of FBXL19 and PDLIM2 proteins or increasing the stability of these ubiquitin ligases will be a strategy for suppressing RANKL in osteocytes. FBXL19 degradation is regulated by FBXW17-mediated ubiquitination and CBP-mediated acetylation 67 , 68 . Manipulating these mechanisms of FBXL19 degradation may be an approach to suppress osteoclastogenesis in bone infection.…”
Section: Discussionmentioning
confidence: 99%
“…Because overexpression of FBXL19 or PDLIM2 suppresses RANKL in osteocytic cells, preventing the reduction of FBXL19 and PDLIM2 proteins or increasing the stability of these ubiquitin ligases will be a strategy for suppressing RANKL in osteocytes. FBXL19 degradation is regulated by FBXW17-mediated ubiquitination and CBP-mediated acetylation 67 , 68 . Manipulating these mechanisms of FBXL19 degradation may be an approach to suppress osteoclastogenesis in bone infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent research showed that FBXW17 ubiquitinates FBXL19 for its degradation. Silence of FBXW17 attenuated lysophosphatidic acid (LPA)-induced epithelial cell migration (Dong et al, 2020), which suggested a potential role of FBXW17 in cell function regulation. Small molecules inhibiting FBXO3 reduce cytokine release and lessen associated inflammatory diseases via destabilizing tumor necrosis factor receptor-associated factor (TRAF) protein (Chen et al, 2013;Mallampalli et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…FBXW17, an ortholog of FBXW12 in mouse genome, is a 466-amino-acid protein containing an F-box motif for the recognition of substrate and the recruitment of ubiquitylation (Jin et al, 2004). As an SCF protein member, FBXW17 has a similar sequence to other FBPs, which is recently reported to ubiquitinate FBXL19 for its degradation (Dong et al, 2020). However, its function and other molecular targets remain to be determined further depending on its role in SCF subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoblastoma (RB), a malignant tumor derived from photoreceptor precursor cells, is usually found in children under 3 years old, with family genetic predisposition. Circ-0075804 promotes RB cell proliferation by binding to heterogeneous ribonucleoprotein K (HNRNPK), thereby increasing the stability of E2F3 mRNA, which indicates that circ-0075804 may become a therapeutic target for RB patients [ 39 ]. Xu found that circVAPA was upregulated in human RB specimens and RB cell lines through qRT-PCR, and was associated with the poor prognosis of RB patients.…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 99%